Results of the NRG Oncology/RTOG 0848 Adjuvant Chemotherapy Question—Erlotinib+Gemcitabine for Resected Cancer of the Pancreatic Head: A Phase II Randomized Clinical Trial. (March 2020) - Abrams, Ross A.; Winter, Kathryn A.; Safran, Howard; Goodman, Karyn A.; Regine, William F.; Berger, Adam C.; Gillin, Michael T.; Philip, Philip A.; Lowy, Andrew M.; Wu, Abraham; DiPetrillo, Thomas A.; Corn, Benjamin W.; et al.
Abstract : Purpose: NRG/RTOG 0848 was designed to determine whether adjuvant radiation with fluoropyrimidine sensitization improved survival following gemcitabine-based adjuvant chemotherapy for patients with resected pancreatic head adenocarcinoma. In step 1 of this protocol, patients were randomized to adjuvant gemcitabine versus the combination of gemcitabine and erlotinib. This manuscript reports the final analysis of these step 1 data. Methods: Eligibility—within 10 weeks of curative intent pancreaticoduodenectomy with postoperative CA19-9<180. Gemcitabine arm—6 cycles of gemcitabine. Gemcitabine+erlotinib arm—gemcitabine and erlotinib 100 mg/d. Two hundred deaths provided 90% power (1-sided α=0.15) to detect the hypothesized OS signal (hazard ratio=0.72) in favor of the arm 2. Results: From November 17, 2009 to February 28, 2014, 163 patients were randomized and evaluable for arm 1 and 159 for arm 2. Median age was 63 (39 to 86) years. CA19-9 ⩽90 in 93%. Arm 1: 32 patients (20%) grade 4 and 2 (1%) grade 5 adverse events; arm 2, 27 (17%) grade 4 and 3 (2%) grade 5. GI adverse events, arm 1: 22% grade ≥3 and arm 2: 28%, ( P =0.22). The median follow-up (surviving patients) was 42.5 months (min-max: <1 to 75). With 203 deaths, the median and 3-year OS (95% confidence interval) are 29.9 months (21.7, 33.4) and 39% (30, 45) for arm 1 and 28.1 months (20.7, 30.9) and 39% (31, 47) for arm 2 (log-rank P =0.62). Hazard ratio (95% confidence interval) comparing OS of arm 2 to arm 1 is 1.04 (0.79, 1.38). Conclusions: The addition of adjuvant erlotinib to gemcitabine did not provide a signal for increased OS in this trial. Abstract : Supplemental Digital Content is available in the text.